Chemical Grinding Aids as Chemical Agents to Enhance the Efficiency of Clinker Grinding in Cement Plants - Akhwan Purwoko; Djoko Setyanto (Fakultas Teknik Universitas Pancasila, 2025)
Chemical Grinding Aids, hereinafter referred to as Grinding Aids, are chemical additives used to optimize the grinding process of clinker and other supplementary materials into cement powder. In practice, these Grinding Aids enhance the efficiency of the grinding process, thereby increasing the capacity of the grinding equipment. As a result of this increased capacity, the electrical energy consumption per ton of cement produced is reduced, leading to a proportional decrease in production costs per ton. In addition to improving productivity, the use of Grinding Aids also contributes to better cement quality. Experimental data presented in this article show that the application of Grinding Aids has a positive impact, increasing production by up to 17% with an optimal dose of 350 ppm when using concentrated Grinding Aids without dilution. Meanwhile, the optimal dose for a Grinding Aid solution diluted in water at a ratio of 1:4 (grinding aids:water) is 300 ppm. This improvement in productivity also leads to a 5% reduction in electricity consumption during the cement grinding process.